Financial and Monetary Policy of Great Britain During the Napoleonic Wars - Silberling, Norman J. (Quarterly Journal of Economics, 1924)
The circumstances attending the Bank Restriction, 398. — Deviations in exchange rates and specie, 398. — Sentiments of Paine, Fox, and Sheridan; their political objectives, 400. — Walter Boyd's statement of a depreciation theory; responsibility attributed solely to the Bank; indices of excessive issue, 404. — Henry Thornton and the purchasing-power-parity theory; confusion between convertible and inconvertible conditions; defense of the Bank, 407. — Horner's interpretation, 411. — Lord King's view of excess and depreciation; disregard of political factors; exoneration of the country banks, 413. — John Wheatley's program for war financing by systematic lowering of prices; refutation of the country-bank doctrine, 415. — Writings of Ricardo; agitation for immediate contraction of Bank issues and possibly resumption of cash payments; theoretical confusions and inconsistencies; hostility to the Bank; possibly explained by stock-exchange interests, 423. — The Bullion Committee Report a theoretical essay divorced from facts, abounding in misconceptions, and proposing impossible policy, 430. — Ricardo's striking change of attitude in 1819, 437.